Cultural Genocide and the Protection of Cultural Heritage - Luck, Edward C. (Getty Publications, 2020)
Cultural Genocide and the Protection of Cultural Heritage examines the various lenses through which the international community defines attacks on cultural heritage-legal, accountability, security, counterterrorism, and atrocity prevention-and proposes a sixth, cultural genocide, that can be used to recast the debate over how to best protect the world's cultural heritage.